Distributed optical fibre sensing for early detection of shallow landslides triggering. Issue 1 (December 2017) - Schenato, Luca; Palmieri, Luca; Camporese, Matteo; Bersan, Silvia; Cola, Simonetta; Pasuto, Alessandro; Galtarossa, Andrea; Salandin, Paolo; Simonini, Paolo
ABSTRACT A distributed optical fibre sensing system is used to measure landslide-induced strains on an optical fibre buried in a large scale physical model of a slope. The fibre sensing cable is deployed at the predefined failure surface and interrogated by means of optical frequency domain reflectometry. The strain evolution is measured with centimetre spatial resolution until the occurrence of the slope failure. Standard legacy sensors measuring soil moisture and pore water pressure are installed at different depths and positions along the slope for comparison and validation. The evolution of the strain field is related to landslide dynamics with unprecedented resolution and insight. In fact, the results of the experiment clearly identify several phases within the evolution of the landslide and show that optical fibres can detect precursory signs of failure well before the collapse, paving the way for the development of more effective early warning systems.